2017
DOI: 10.1093/alcalc/agx035
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Glucuronide Elimination Kinetics in Fingernails and Comparison to Levels in Hair

Abstract: Nails are an alternative matrix to hair when measuring ethyl glucuronide (EtG). The present study indicate that EtG cut-off levels in nails should be higher compared to the established 30 pg/mg EtG cut-off in hair representing heavy drinking, and EtG may disappear faster from nail than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Such EtG wash‐out effects have been proposed in previous studies as a mechanism of EtG elimination from hair. Potential wash‐out of EtG in nail have also been proposed as a possible explanation in a previously published study which showed that EtG disappeared from nails faster than it was otherwise assumed from nail growth only. Although that study used nail as a matrix, the incorporation and elimination of mechanisms is to some extent comparable to hair.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Such EtG wash‐out effects have been proposed in previous studies as a mechanism of EtG elimination from hair. Potential wash‐out of EtG in nail have also been proposed as a possible explanation in a previously published study which showed that EtG disappeared from nails faster than it was otherwise assumed from nail growth only. Although that study used nail as a matrix, the incorporation and elimination of mechanisms is to some extent comparable to hair.…”
Section: Discussionmentioning
confidence: 96%
“…no 2013/1222). For the first 16 of the 27 patients included in the present study, longitudinal nail EtG data were also collected …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hair EtG (hEtG) reflects the alcohol consumption in the past months, depending on the analyzed hair length taking into account the growth rate of hair of approximately 1 cm/month (Crunelle et al, 2014; Pragst and Balikova, 2006). Nails grow significantly slower than hair, resulting in higher absolute concentration of EtG in nails than in hair (Fosen et al, 2017). Fosen and colleagues investigated the elimination kinetics of EtG in nail clippings in forty patients in alcohol rehabilitation.…”
Section: Figmentioning
confidence: 99%
“…Fosen and colleagues investigated the elimination kinetics of EtG in nail clippings in forty patients in alcohol rehabilitation. The half-life of nail EtG was 13.3 days (range: 5.5 to 29) and patients (n = 22) who reached negative nail EtG during the study period did that after 47.0 days (range: 13-60; Fosen et al, 2017).…”
mentioning
confidence: 99%